Adenovirus-induced kidney graft pyelonephritis following renal transplantation - Tomoe, H (Hinyokika kiyo. Acta urologica Japonica, 1994)
A 16-year-old female received a kidney transplantation from her mother 13 months before she suddenly noticed gross hematuria and painful micturition, and developed high fever with chills. The serum creatinine (S-Cr) level rose from 1.5 to 2.6 mg/dl, but there was no clinical sign of acute rejection. Despite the treatment with antibiotics and gamma-globulin, the the high fever and hematuria did not improve. The adenovirus antibody titer elevated from x8 to x1,024, while adenovirus was not isolated from the urine. On the 15th day of the disease, hematuria disappeared spontaneously and on the 19th day she became afebrile. The S-Cr level also was normalized spontaneously. Histological examination of the graft biopsy on the 14th day, showed severe tubulointerstitial nephritis localized in the renal medulla and full type intranuclear inclusions were revealed in tubular epithelial cells. From these findings, we diagnosed this case as adenovirus-induced kidney graft pyelonephritis associated with acute hemorrhagic cystitis